The role of firm dynamics in the green transition: Carbon productivity decomposition in Finnish manufacturing - Kuosmanen Natalia; Maczulskij Terhi (The Research Institute of the Finnish Economy (ETLA), 2022)
This paper investigates the importance of firm dynamics, including entry and exit and the allocation of carbon emissions across firms, on the green transition. Using the 2000-2019 firm-level register data on greenhouse gas emissions matched with the Financial Statement data in the Finnish manufacturing sector, we examine the sources of carbon-productivity growth and assess the relative contributions of structural change and firm dynamics. We find that continuing firms were the main drivers of carbon productivity growth whereas the contribution of entering and exiting firms was negative. In addition, the allocation of emissions across firms seems to be inefficient; its impact on carbon productivity growth was negative over the study period. Moreover, we find that there is a positive relationship between labor-intensive firms and carbon productivity but that firms with a larger market share tend to be less productive in terms of carbon use.
Keywords: D24; L60; Q54; 330; Carbon productivity; Decomposition; Firm dynamics; Firm-level data; Manufacturing